DISAIN LEMBAGA PEMBIAYAAN PERTANIAN NASIONAL SUBSEKTOR TANAMAN PANGAN MENGGUNAKAN PENDEKATAN INTEPRETATIVE STRUCTURAL MODELING (ISM) - Imam Teguh Saptono; Marimin Marimin; Mangara Tambunan; Rina Oktaviani (School of Business, Bogor Agricultural University (SB-IPB), 2010)
In year 2009, the agricultural sector contributed around 15% of Indonesia’s GDP, and absorbed around 44 million of total workforce. As the biggest GDP contributor and workforce absorption within the sector, foodcrops holds a strategic role in providing national food security. In line with ensuring food security program government has promulgated a national agricultural revitalization agenda, which one of the programs is providing a financing scheme for small scale farmer. At the implementation level, the program was not performed yet, due to the weaknesses of existing institutions.In turn it resulted in the significant gap of financing and investment in the agricultural sector. The aim of this research is to design a model of financial institution a nation wide level, focussing on foodcrops financing using Interpretative Structural Modeling (ISM) which then supported by Analytical Hierarchy Process (AHP). The combination of ISM, systems approach and AHP are designated to accommodate the complexity of the object. The respondents involved are experts from various related institutions. ISM analysis indicated that price stability, government commitment, geographic coverage, suitability of the institution with local conditions, and return of investment are strong sub-elements drivers among the sub-elements of the system. The recommendation of institution design by using AHP is to develop a new non-bank financial institution, set up by the government that focuses their financing baesd on supply chain approach. (Key words: Financial Institution, Foodcrops, ISM, AHP)